E-commerce dalam perspektif fiqh muamalat - Larasati Dhinarti; Firda Amalia (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The development of information technology has had a real impact on business innovation. E-commerce is one of the innovations in the business world in Indonesia. This study aims to analyze the practice of e-commerce from the perspective of Fiqh Muamalat. The research method used is a literature study with a qualitative approach. This study found that e-commerce is an identical buying and selling practice with the practice of salam. This e-commerce practice can also be justified if it fulfills matters into obligations in the practice of salam.